Pilot Study Evaluating Regulatory T Cell–Promoting Immunosuppression and Nonimmunogenic Donor Antigen Delivery in a Nonhuman Primate Islet Allotransplantation Model. Issue 10 (26th May 2015) - Lei, J.; Kim, J. I.; Shi, S.; Zhang, X.; Machaidze, Z.; Lee, S.; Schuetz, C.; Martins, P. N.; Oura, T.; Farkash, E. A.; Rosales, I. A.; Smith, R. N.; et al.
<x xml:space="preserve">Abstract</x> The full potential of islet transplantation will only be realized through the development of tolerogenic regimens that obviate the need for maintenance immunosuppression. Here, we report an immunotherapy regimen that combines 1‐ethyl‐3‐(3′‐dimethylaminopropyl)‐carbodiimide (ECDI)‐treated donor lymphoid cell infusion (ECDI‐DLI) with thymoglobulin, anti‐interleukin‐6 receptor antibody and rapamycin to achieve prolonged allogeneic islet graft survival in a nonhuman primate (NHP) model. Prolonged graft survival is associated with Treg expansion, donor‐specific T cell hyporesponsiveness and a transient absence of donor‐specific alloantibody production during the period of graft survival. This regimen shows promise for clinical translation.